The Implementation of Effective Online Asynchronous Corrective Feedback on the Oral Production of English as a Foreign Language Learners in University Virtual Speaking Classes (Innovaciones Educativas, 2023)
This article had as main aim that of identifying the effectiveness of asynchronous corrective feedback on the oral production of university students taking an online integrated English course as part of their program. All research instruments and tested corrective feedback method were applied in the speaking section of the course that had a duration of sixteen weeks. The study followed a mixed-methods design, where qualitative data was gathered by means of a leaners’ speech analysis scale, while quantitative data was gathered through a questionnaire addressing language learners´ preferences in relation to corrective feedback in oral English classes. A first oral test and final oral test were also used as pre-test and post-test to measure the level of improvement after the intervention phase. Opposed to Nunan’s (1992) position towards the use of positive feedback instead of corrective feedback, the present research project was underlaid by the conception that teachers’ reactions and reflections on learners’ deviant forms of the target language are a crucial part of the whole language learning spectrum.  Very interesting findings were shed, first, for the two main types of errors analyzed in the study (Grammar and Vocabulary, and Pronunciation), there was a diminution in quantity when comparing the results from the first exam to those of the final exam, representing those learners committed 10% less errors in the final oral exam.  Unsurprisingly, students unanimously favored the use of corrective feedback in their language classes. However, preferences on synchronous and asynchronous corrective feedback showed no major difference.
Keywords: Feedback; Electronic Learning; Second Language Instruction; Oral Expression; University Students